(untitled) - Hastuti, Heni; Nisa, Zahra Dzakiyatin; Umma, Husnia Auliyatul; Putri, Anak Agung Alit Kirti Estuti Narendra; Mashuri, Yusuf Ari (Journal of Maternal and Child Health, 2020)
Background: Children are categorized as short stature when the Height for Age results are below the 3rd percentile of CDC growth chart standard. Short stature on children will have an impact on increased mortality and morbidity, children